On credibility of simulation studies of telecommunication networks. - Pawlikowski, K. (IEEE Communications magazine)
In telecommunication networks, as in many other areas of science and engineering, the proliferation of computers as research tools has resulted in the adoption of computer simulation as the most commonly used paradigm of scientific investigations. This, together with a plethora of existing simulation languages and packages, has created a popular opinion that simulation is mainly an exercise in computer programming. In new computing environments, programming can be minimized, or even fully replaced, by the manipulation of icons (representing prebuilt programming objects containing basic functional blocks of simulated systems) on a computer monitor. One can say that we have witnessed another success of modern science and technology: the emergence of wonderful and powerful tools for exploring and predicting the behavior of such complex stochastic dynamic systems as telecommunication networks. But this enthusiasm is not shared by all researchers in this area. An opinion is spreading that one cannot rely on the majority of the published results on performance evaluation studies of telecommunication networks based on stochastic simulation, since they lack credibility. Indeed, the spread of this phenomenon is so wide that one can speak about a deep crisis of credibility. In this article this claim is supported by the results of a survey of over 2200 publications on telecommunication networks in proceedings of IEEE INFOCOM and such journals as IEEE Transactions on Communications, IEEE/ACM Transactions on Networking, and Performance Evaluation Journal. The discussion focuses on two important necessary conditions of a credible simulation study: use of appropriate pseudo-random generators of independent uniformly distributed numbers, and appropriate analysis of simulation output data. Having considered their perils and pitfalls, we formulate guidelines that, if observed, could help to ensure a basic level of credibility of simulation studies of telecommunication networks